2017
DOI: 10.1139/cjpp-2016-0619
|View full text |Cite
|
Sign up to set email alerts
|

Kallikrein–kinin system as the dominant mechanism to counteract hyperactive renin–angiotensin system

Abstract: The renin–angiotensin system (RAS) generates, maintains, and makes worse hypertension and cardiovascular diseases (CVDs) through its biologically active component angiotensin II (Ang II), that causes vasoconstriction, sodium retention, and structural alterations of the heart and the arteries. A few endogenous vasodilators, kinins, natriuretic peptides, and possibly angiotensin (1-7), exert opposite actions and may provide useful therapeutic agents. As endothelial autacoids, the kinins are potent vasodilators, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 95 publications
0
13
0
1
Order By: Relevance
“…Oxidative stress characterized by an excessive production of RAS byproducts, ROS and NADPH oxidase (Nox) along with matrix metalloproteinase-9 (MMP-9), cytosolic phospholipase A2 (cPLA2), cyclooxygenase-2 (COX-2), iNOS induced by proinflammatory factors such as cytokines, interleukins (IL) and peroxidants is usually thought to be responsible for tissue injury associated with a range of brain injury, inflammation, and degenerative diseases (Theodoropoulos and Loumos 1991, Abbott 2000, Stegbauer, Lee et al 2009, Uttara, Singh et al 2009, Labandeira-Garcia, Rodriguez-Perez et al 2017, Regoli and Gobeil 2017). A recent work by Yang et al highlighted the contribution of BK in enhancing the production and release of different molecules mediating apoptotic cell death from astrocytes (Yang, Hsieh et al 2013).…”
Section: The Kallikrein-kinin System and Its Role In The Brainmentioning
confidence: 99%
“…Oxidative stress characterized by an excessive production of RAS byproducts, ROS and NADPH oxidase (Nox) along with matrix metalloproteinase-9 (MMP-9), cytosolic phospholipase A2 (cPLA2), cyclooxygenase-2 (COX-2), iNOS induced by proinflammatory factors such as cytokines, interleukins (IL) and peroxidants is usually thought to be responsible for tissue injury associated with a range of brain injury, inflammation, and degenerative diseases (Theodoropoulos and Loumos 1991, Abbott 2000, Stegbauer, Lee et al 2009, Uttara, Singh et al 2009, Labandeira-Garcia, Rodriguez-Perez et al 2017, Regoli and Gobeil 2017). A recent work by Yang et al highlighted the contribution of BK in enhancing the production and release of different molecules mediating apoptotic cell death from astrocytes (Yang, Hsieh et al 2013).…”
Section: The Kallikrein-kinin System and Its Role In The Brainmentioning
confidence: 99%
“…In addition, the kallikrein–kinin system (KKS) could lower blood pressure and negatively regulate RAS. In the KKS, kininogen is degraded into kinin, which is helpful for controlling the blood pressure (Regoli & Gobeil, ). It was reported that nattokinase could lower the blood pressure and had impact on the renin activity (Kim et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…B2Rs are constitutively expressed in several tissues, including skeletal muscle, while B1Rs are upregulated upon damage or inflammation. Frequently, the effects mediated by BK via B2 receptors are opposite to those of the classical axis of the RAS, being a potent vasorelaxant and antihypertensive agent [ 152 ]. RAS and KKS have different crosstalk points, where ACE is pivotal because it produces Ang-II and degrades BK.…”
Section: Regulation Of Ccn2/ctgf and Fibrosis In Skeletal Muscle: Role Of Vasoactive Peptidesmentioning
confidence: 99%